2009
DOI: 10.1007/s00127-009-0501-y
|View full text |Cite
|
Sign up to set email alerts
|

From childhood to adult age: 18-year longitudinal results and prediction of the course of mental disorders in the community

Abstract: These data spanning almost two decades add significant information to the existing literature on the course of mental disorders in the community during the transition from adolescence to adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 36 publications
3
43
0
6
Order By: Relevance
“…That is, it is conceivable that certain risk factors for depression have direct or indirect relations to attentional control and rumination. For instance, sleep disturbances are a well-established risk factor for depression, that are not only present during depressive episodes but also precede these episodes (Fichter, Kohlboeck, Quadflieg, Wyschkon, & Esser, 2009). In relation to the framework presented here, one could hypothesize that sleep disturbances may be related to depression through its influence on attentional control and rumination.…”
Section: Future Challenges Understanding Depressive Rumination 21mentioning
confidence: 88%
“…That is, it is conceivable that certain risk factors for depression have direct or indirect relations to attentional control and rumination. For instance, sleep disturbances are a well-established risk factor for depression, that are not only present during depressive episodes but also precede these episodes (Fichter, Kohlboeck, Quadflieg, Wyschkon, & Esser, 2009). In relation to the framework presented here, one could hypothesize that sleep disturbances may be related to depression through its influence on attentional control and rumination.…”
Section: Future Challenges Understanding Depressive Rumination 21mentioning
confidence: 88%
“…Recent studies have established high comorbidity rates between sleep disturbances and anxiety (Alfano et al, 2007;Spoormaker and van den Bout, 2005;Taylor et al, 2005), rates which vary across different anxiety disorders (Johnson et al, 2006). Longitudinal associations have also been established between sleep disturbances, anxiety, and depression (Baglioni et al, 2011;Fichter et al, 2009). Emerging research on this association in psychosis shows sleep disturbance to be a significant predictor of psychosis (Lunsford-Avery et al, 2013;Zanini et al, 2013), even when controlling for depression (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…This finding has been observed mainly among adults. Prior research, however, suggests that there are grounds to examine the persistence of the association between low SES during adolescence and adulthood depression [e.g., 8]. A meta-analysis of both cross-sectional and longitudinal studies has shown long-lasting consequences of SES [9].…”
Section: Introductionmentioning
confidence: 99%